Pregunta
upstudy study bank question image url

9. Without using a calculator, find the value of \( p \) such that \( \left(\frac{2}{\sqrt{75}}-\frac{\sqrt{147}}{3}\right) \div \sqrt{2}=p \sqrt{6} \).

Ask by Bolton Bond. in Singapore
Feb 15,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( p = -\frac{11}{10} \)

Solución

We start with the expression   (2/√75 – √147/3) ÷ √2 = p√6. Step 1. Simplify the square roots in the fractions. • √75 = √(25×3) = 5√3, so   2/√75 = 2/(5√3). • √147 = √(49×3) = 7√3, so   √147/3 = (7√3)/3. Step 2. Write the expression as   [2/(5√3) – 7√3/3] ÷ √2. Step 3. To combine the two terms inside the parentheses, rationalize the first term:   2/(5√3) = (2√3)/(5×3) = 2√3/15, and express the second term with denominator 15:   7√3/3 = (35√3)/15. Thus, the numerator becomes   (2√3/15 – 35√3/15) = –33√3/15, which can be simplified to   –11√3/5. Step 4. Now, the expression is   (–11√3/5) ÷ √2 = –11√3/(5√2). Step 5. Rationalize the denominator by multiplying the numerator and denominator by √2:   –11√3/(5√2) = –11√3√2/(5×2) = –11√6/10. This is of the form p√6 with   p = –11/10. Thus, the value of p is –11/10.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To solve for \( p \) in the equation \[ \left(\frac{2}{\sqrt{75}} - \frac{\sqrt{147}}{3}\right) \div \sqrt{2} = p \sqrt{6}, \] we first simplify the left-hand side of the equation. 1. Simplifying \( \sqrt{75} \): \[ \sqrt{75} = \sqrt{25 \cdot 3} = 5\sqrt{3}. \] Thus, \[ \frac{2}{\sqrt{75}} = \frac{2}{5\sqrt{3}}. \] 2. Simplifying \( \sqrt{147} \): \[ \sqrt{147} = \sqrt{49 \cdot 3} = 7\sqrt{3}. \] Therefore, \[ \frac{\sqrt{147}}{3} = \frac{7\sqrt{3}}{3} = \frac{7}{3} \sqrt{3}. \] 3. Now substituting these simplifications into the expression: \[ \frac{2}{5\sqrt{3}} - \frac{7\sqrt{3}}{3}. \] To subtract these fractions, we need a common denominator. The least common multiple of \( 5\sqrt{3} \) and \( 3 \) is \( 15\sqrt{3} \). Rewriting the first term: \[ \frac{2}{5\sqrt{3}} = \frac{2 \cdot 3}{5 \cdot 3\sqrt{3}} = \frac{6}{15\sqrt{3}}. \] Rewriting the second term: \[ \frac{7\sqrt{3}}{3} = \frac{7\sqrt{3} \cdot 5\sqrt{3}}{3 \cdot 5\sqrt{3}} = \frac{35(\sqrt{3})^2}{15\sqrt{3}} = \frac{105}{15\sqrt{3}}. \] 4. Now we can perform the subtraction: \[ \frac{6}{15\sqrt{3}} - \frac{35}{15\sqrt{3}} = \frac{6 - 35}{15\sqrt{3}} = \frac{-29}{15\sqrt{3}}. \] 5. Next, divide this result by \( \sqrt{2} \): \[ \left(\frac{-29}{15\sqrt{3}}\right) \div \sqrt{2} = \frac{-29}{15\sqrt{3}} \cdot \frac{1}{\sqrt{2}} = \frac{-29}{15\sqrt{6}}. \] 6. Now, we express this as \[ p\sqrt{6}. \] To make the left-hand side in the same form, multiply the numerator and the denominator by \( \sqrt{6} \): \[ \frac{-29\sqrt{6}}{15\cdot 6} = \frac{-29\sqrt{6}}{90}. \] 7. Setting this equal to \( p\sqrt{6} \), \[ p\sqrt{6} = \frac{-29\sqrt{6}}{90}. \] This implies that \[ p = \frac{-29}{90}. \] Thus, the value of \( p \) is \[ \boxed{\frac{-29}{90}}. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad